The Effect of teach-back educational method on self-management in hemodialysis patients - Fani, Rif'atul; Wahyusari, Shinta; Hastuti, Apriyani Puji; Al Husna, Chairul Huda (University of Muhammadiyah Malang, 2025)
Introduction: Patients with chronic kidney disease undergoing hemodialysis may experience a decline in physical and psychological conditions such as increased risk of depression and non-compliance in undergoing therapy. Therefore, proper self-management is needed so that patients can control their disease. Teach-back education is one interactive method that can be used to improve self-management of hemodialysis patients. Objectives: The purpose of this study was to determine the effect of the teach-back educational method on self-management in hemodialysis patients. Methods: This study used a quasi-experimental design with a pre-test and post-test design, for 137 end-stage renal disease patients undergoing hemodialysis at Wava Husada Hospital. The duration of the training was 3 sessions and the time of each session ranged from 45 minutes to one hour. To collect data from patients, a demographic questionnaire and the Hemodialysis Self-management Instrument-18 (HDSMI-18) were used to assess patient self-management before and after the intervention. A significance level of 5% was established for the analysis. Results: The overall self-management score before intervention was 53.47 ± 8.59. The total score of self-management after intervention was 57.15 ± 8.94. Data analysis indicated that the difference in the mean score of self-management before and after teach-back education was significant (p = 0.000). Among the dimensions of self-management, there was a significant difference for two dimensions including self-care and problem-solving before and after teach-back education (p = 0.000).Conclusions: The teach-back educational method was effective in improving self-management in hemodialysis patients. It improved self-management in the dimensions of self-care and problem-solving. It is recommended that nurses in hemodialysis units implement teach-back education as a routine practice in caring for hemodialysis patients.